DAMPAK CG PADA CSRD DAN PENGARUHNYA TERHADAP PROFITABILITAS SEKTOR PERTAMBANGAN SYARIAH BEI - Henny Ariani; Muhammad Umar Mai (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2021)
The study aims to investigate the impact of corporate governance on corporate social responsibility disclosure (CSRD) and the effect of CSRD to the profitability. The samples to study was gained from annual-report of the 29 firms that listed in Sharia’s critheria issued by the Bursa Efek Indonesia (BEI) in the Mining Sector Companies, from 2015 to 2019. The study will conduct by using the Partial Least Square-Structural Equation Modelling (PLS-SEM) using Warp-PLS software. The results of this study indicate that corporate governance proxied by variabels such as institutional ownership, board independent, and board of directors size have positive impact and significant to CSRD. Thus, The results have indicated that CSRD have positive impact and significant to profitability. This study contribute to the development of corporate governance’s theory especially on the CSRD activities within the mining sectors companies with Sharia Critheria. Otherwise, this study gives new widen perspective to the managements and investors on the mining sectors companies with Sharia Critheria. In bound of the corporate governance, CSRD activities , and the profitability achievements.